Geology of the southern Gran Paradiso Massif and Lower Piedmont Zone contact area (middle Ala Valley, Western Alps, Italy). Issue 2 (1st December 2021) - Caso, F.; Nerone, S.; Petroccia, A.; Bonasera, M.
ABSTRACT: This work presents the structural evolution of a poorly studied key-area in the middle Ala Valley, Western Alps, where two tectono-metamorphic units are exposed. A geological map at the 1:10.000 scale, integrated with meso- and microstructural analysis, has been realised. We investigated the contact area between Gran Paradiso Massif in the footwall and Lower Piedmont Zone in the hanging wall. Both tectono-metamorphic units, with a different paleogeographic affinity, preserve similar polyphasic deformation histories, defined by four deformation phases. The Dp phase, strongly transposing previous structural relicts, is marked by a high-pressure assemblage associated with the Sp foliation. Dp controls the lithological boundary attitude. A mylonitic zone, developed during the Dp, showing kinematic indicators pointing to a top-to-the N-NW sense of shear, is responsible for the juxtaposition of the two units. Dp structural elements are deformed by Dp+1 and Dp+2 subsequent phases. A greenschist-facies overprinting was observed during the Dp+1 phase.